Occupational Pesticide Exposure and Parkinsonism Symptoms Among Highland Vegetable Farmers in North Sumatra, Indonesia: A Cross-Sectional Study - Suriati Lubis; Dwi Ris Hasanah S (Media of Health Research, 2025)
Chronic pesticide exposure is an established environmental risk factor for parkinsonian syndromes, yet evidence from Southeast Asian smallholder agriculture is scarce. This community-based cross-sectional study examined the prevalence of Parkinsonism symptoms and modifiable occupational determinants among 102 pesticide-applying farmers in Juhar District, Karo Regency, North Sumatra, Indonesia. Parkinsonism symptoms were screened using an adapted Unified Parkinson's Disease Rating Scale motor checklist (Cronbach α = 0.89). Exposure intensity, personal protective equipment (PPE) use, and post-application hygiene were assessed through structured interviews. Associations were tested using chi-square analysis and crude odds ratios (OR) with 95% confidence intervals (CI). Screening-positive Parkinsonism symptoms were identified in 36 farmers (35.3%; 95% CI 26.2–45.2), including resting tremor, bradykinesia, rigidity, and postural instability. High spraying frequency (OR = 7.1; 95% CI 2.7–18.9; p = 0.001), inconsistent PPE use (OR = 4.7; 95% CI 1.8–12.0; p = 0.002), and inadequate hygiene (OR = 7.5; 95% CI 2.5–22.0; p < 0.001) were all strongly associated with symptom positivity. One in three pesticide-applying farmers screened positive for Parkinsonism symptoms in this highland horticultural community, with strong associations to modifiable occupational behaviours. Findings support integrated occupational-health action including subsidised PPE, farmer education, restriction of highly hazardous pesticides such as paraquat, and neurological screening at primary care.